Pengaruh Strategi Branding Media Sosial dan Persepsi Merek terhadap Minat Beli Konsumen Masyarakat Generasi Z (Studi pada Produk Skincare Ms Glow Di Kel. Tulusrejo Kec. Lowokwaru Kota Malang) - Dina, Zakiyatul Rohmah; Djaelani, Abdul Kodir; Normaladewi, Andi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims analyze the influence of social media branding strategies and brand perception on Generation Z consumers' purchase intention for MS Glow skincare products in Tulusrejo Village, Lowokwaru District, Malang City. With the increasing use of social media as a marketing platform, effective branding strategies have become a key factor in attracting consumer attention and shaping a positive brand perception. Generation Z, as a digitally active group, is highly influenced by social media-based marketing content, user testimonials, and the brand image built online. This research employs a quantitative approach using a survey method through questionnaires distributed to 75 respondents who are Generation Z consumers who have purchased MS Glow products. Data analysis was conducted using multiple linear regression tests to examine the relationship between the independent variables (social media branding strategy and brand perception) and the dependent variable (purchase intention). The findings indicate that social media branding strategies and brand perception simultaneously have a significant influence on purchase intention. Partially, social media branding strategies positively impact purchase intention, with key success factors including consistent communication, customer interaction, and engaging visual content. Additionally, brand perception, which reflects quality, credibility, and trust, also contributes to increasing consumers' purchasing decisions. Thus, companies need to optimize their digital marketing strategies and maintain a strong brand image to enhance product attractiveness among Generation Z consumers. Keywords: Social Media Branding Strategy, Brand Perception, Purchase Intention, MS GLOW Skincare..